HEMOSTASIS DISORDERS WITH ABNORMAL UTERINE BLEEDING AND THEIR TREATMENT TACTICS - Kachailo, I.A.; Kuzmina, I.Yu. (World of Medicine and Biology, 2024)
To determine the specifics of hemostasis disorders in abnormal uterine bleeding, we examined 130 women, of which 110 were female patients who made up the main group. The control group included 20 healthy women without menstrual cycle disorders. It was found that abnormal uterine bleeding in the reproductive age, in the absence of etiopathogenetic treatment, leads to the development of posthemorrhagic anemia. The severity and nature of bleeding are determined by defects in the platelet link system of the hemostasis system that violate the aggregation function of platelets. The study of the overall hemostatic potential, primary hemostasis, and the state of intravascular coagulation in patients with abnormal uterine bleeding using methods for assessing the amount of platelet aggregation allowed us to identify and differentiate disorders in the hemostasis system. The application of modern principles of management of women with abnormal uterine bleeding and the use of fibrinolysis inhibitors allows for an increase in the activity of the blood coagulation system and to stop bleeding for 2–5 days altogether.
Keywords: abnormal uterine bleeding; disorders of the coagulation system; overall hemostatic potential; fibrinolysis inhibitors